A functional polymorphism in the promoter region of miR‐155 predicts the risk of intracranial hemorrhage caused by rupture intracranial aneurysm. Issue 11 (24th July 2019) - Yang, Xiaobo; Peng, Jianhua; Pang, Jinwei; Wan, Weifeng; Chen, Ligang
Abstract: Background: This study aimed to study the effect and underlying molecular mechanisms of single‐nucleotide polymorphism (SNP) rs767649 during the pathogenesis of intracranial aneurysm (IA) rupture. Method: Real‐time PCR and Western blot analysis were performed to detect the differentiated expression of miR‐155 and matrix metalloproteinase‐2 (MMP‐2) among different sample groups. Computational analysis and luciferase assay were conducted to study the effect of SNP rs767649 on the expression of miR‐155 as well as the regulatory relationship between miR‐155 and MMP‐2. Results: In unruptured IA samples, the expression of miR‐155 was upregulated while the expression of MMP‐2 was downregulated compared with the ruptured IA samples. Similarly, the expression of miR‐155 was upregulated while the expression of MMP‐2 was downregulated in samples genotyped as AA/AT compared with samples genotyped as TT. In addition, compared with the negative controls, the luciferase activities of cells treated with rs767649A and rs767649T were both elevated with rs767649A‐transfected cells expressing the highest luciferase activity. Furthermore, a negative relationship was established between miR‐155 and MMP‐2 by measuring the luciferase activity of cells cotransfected with miR‐155 and the wild‐type 3′‐untranslated region of MMP‐2. Conclusion: The results of this study showed that the SNP rs767649 in the promoter of miR‐155 could reduce the transcription activity of miR‐155, while poorly expressed miR‐155 could increase the incidence of IA rupture by increasing the expression of MMP‐2, especially in subjects carrying the TT genotype of SNP rs767649. Abstract : This study aimed to study the effect and underlying molecular mechanisms of single‐nucleotide polymorphism (SNP) rs767649 during the pathogenesis of intracranial aneurysm (IA) rupture. The results of this study showed that the SNP rs767649 in the promoter of miR‐155 could reduce the transcription activity of miR‐155, while poorly expressed miR‐155 could increase the incidence of IA rupture by increasing the expression matrix metalloproteinase‐2 (MMP‐2), especially in subjects carrying the TT genotype of SNP rs767649.